Stem cells and their “niche” in the human heart: toward cell therapies of cardiac disease - Lerman, Daniel Alejandro (The University of Edinburgh, 2019)
Replacement of dead cardiomyocytes by scar tissue, unable to mediate normal cardiac contraction, is the most dramatic change following heart infarction. Current dogma investigates potential endogenous “self-repairing” capacity of the myocardium as a means to minimize such degenerative process. Spontaneous regeneration of the myocardium could be exploited to treat severe and frequently fatal conditions. Post ischaemic intrinsic cardiac healing capability could arise because: i) Cardiomyocytes may proliferate and regenerate damaged tissue, or; i) Endogenous cardiac stem cells (CSCs) may divide and differentiate to exhibit cardiac repairing potential. Although CSCs existence has been documented, their identity, intra-cardiac localization and exact potential remain elusive. Cardiac pericytes, which ensheath blood vessels and express cardiac repair capabilities, could interact with c-kit+ CSCs nested in vascular niches during cellular response to injury. I tested the hypothesis that pericytes and endogenous cardiac progenitor’s stem cells might increase their interaction within vascular niches under ischaemic conditions. Focussing on the potential of cell therapies of cardiac disease, I investigated the spatial relationship between pericytes and endogenous cardiac progenitors within stem cells' niches localised in different regions of the human foetal, adult healthy and ischaemic heart. Immunostaining of foetal human cardiac tissues showed that c-kit+ cells expression and their association with pericytes decrease with heart development. Clear decrease is already evident by 19th week of the gestation. Pericytes and c-kit+ cell populations isolated from foetal hearts and expanded in culture reveal that pericytes’ cells express higher levels of the mesodermal cardiac progenitor factor KDR: 3751± 61(SD) vs 398± 19.9 (SD); (P< 0.05) and for the marker towards cardiac lineage Islet1: 1146±155 (SD) vs 728± 124 (SD); (P< 0.05) while c-kit+ cells express higher levels than pericytes of the stemness marker SSEA3:1655± 40.6 (SD) vs 747± 27 (SD); (P< 0.05), known to progressively decrease with cell differentiation. Absence of staining for CD31 marker in cultured cardiac pericytes and c-kit+ cells is replicated by results of endothelial differentiation assessment, which shows that cardiac pericytes and c-kit+ cells do not form CD31+ networks. The cardiac marker α-actin was present in both cell populations. In healthy adult heart, pericytes marker CD146 localise within the vasculature. Following ischaemia this pericyte marker becomes also evident outside the vasculature. In healthy adult atrium, c-kit expression is low and coexpression with other markers inconspicuous. Ischaemia leads to increased c-kit expression in the microvasculature. Furthermore, following ischaemia c-kit, endothelium and pericyte markers colocalize within the same atrial cells. Colocalization studies in ischaemic hearts revealed low levels of co-occurrence (M1/M2) between c-kit and vascular markers in vessels <50μm but a high degree of correlation (PCC). Ischaemia leads to increased c-kit expression, particularly in blood vessels <50um diameter. Blood vessels >50μm diameter show mostly, staining for endothelial (vWF) and pericyte (CD146) markers. Acute ischaemia of the left ventricle affected the detection of cardiac stem cells markers in the infarcted area. The absence of coexpression of markers during acute ischaemia of the left ventricle suggests that post-ischaemia markers coexpresion is time dependent. CONCLUSION: Foetal heart pericytes and c-kit+/CD117 cells express early cardiac transcription factors and show trans-differentiation potential, which decreases in healthy adult hearts. The preservation and activity of cardiac stem cells’ niches within the atrium vasculature, appears re-activated in post-ischaemic hearts. Better understanding of cardiac c-kit+ and pericyte cells’ interactions during-human embryonic development and during ischaemia may identify alternative novel therapeutic strategy against coronary artery disease.
Keywords: Cardiac regeneration; c-kit; pericytes; human heart; cardiac repair